TAZKIYATUN NAFS: KAJIAN TEORITIS KONSEP AKUNTABILITAS - Prasetio, Januar Eko (Jurnal Analisa Akuntansi dan Perpajakan, 2017)
The concept of accountability is the obligation to account or answer theperformance and actions of a person / legal entity / leadership of an organizationto the party who has the right or obligation to ask for accountability. The conceptof accountability has entered full rationality values that need to be done tazkiyatunnafs based on Islam.